The Role of Vocational Education in Poverty Alleviation Among Rural Dwellers in Nigeria - Ebimieowei Barakabo; Solomon Emmanuel (Goodwood Publishing, 2026)
Purpose: This study evaluates the contribution of vocational education to poverty reduction in rural Nigeria. It focuses on how vocational training enhances employment opportunities and fosters self-sufficiency, thereby helping rural communities transition from subsistence farming to more sustainable and profitable agricultural businesses. Research Methodology: The research uses a qualitative approach, analyzing secondary data from textbooks, academic journals, and government publications. Guided by the Human Capital Theory, it explores how investments in education and training can improve economic outcomes. Results: The findings highlight that challenges like inadequate infrastructure and limited funding hinder vocational education’s full potential. However, it has shown promise in transitioning rural communities from subsistence farming to value-added agricultural businesses, thus increasing household incomes and local economic growth. Conclusions: Vocational education can significantly contribute to poverty reduction in rural Nigeria, provided there is substantial government investment and improved infrastructure. Limitations: The study relies on secondary data, which may not reflect the most recent developments or local experiences, limiting the scope of the findings. Contributions: This study underscores the importance of investing in vocational education to address poverty in rural areas. It recommends enhancing infrastructure, increasing government funding, and fostering industry partnerships to improve vocational training outcomes.